1997
DOI: 10.1128/mcb.17.8.4859
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of the Acute Promyelocytic Leukemia PML-Retinoic Acid Receptor α (RARα) and PLZF-RARα Fusion Proteins on Retinoic Acid Signalling

Abstract: Fusion proteins involving the retinoic acid receptor alpha (RAR alpha) and the PML or PLZF nuclear protein are the genetic markers of acute promyelocytic leukemias (APLs). APLs with the PML-RAR alpha or the PLZF-RAR alpha fusion protein are phenotypically indistinguishable except that they differ in their sensitivity to retinoic acid (RA)-induced differentiation: PML-RAR alpha blasts are sensitive to RA and patients enter disease remission after RA treatment, while patients with PLZF-RAR alpha do not. We here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
114
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 48 publications
(67 reference statements)
3
114
0
Order By: Relevance
“…This agrees with recent ®ndings showing that pharmacological concentrations of RA cause the release of the corepressorhistone deacetylase complex from PML/RARa Lin et al, 1998;He et al, 1998). Likewise, RA treatment of U937 cells induces, in the presence of PML/RARa expression, a dramatic increase in the activation of certain RA-target genes, for example transglutaminase type II and RARb (Ruthardt et al, 1997). Notably, the biological e ects of the mutants are in agreement with their RAdependent transcription factor action, since biologically active mutants have a transactivating activity similar to that of PML/RARa and increased with respect of that of RAR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This agrees with recent ®ndings showing that pharmacological concentrations of RA cause the release of the corepressorhistone deacetylase complex from PML/RARa Lin et al, 1998;He et al, 1998). Likewise, RA treatment of U937 cells induces, in the presence of PML/RARa expression, a dramatic increase in the activation of certain RA-target genes, for example transglutaminase type II and RARb (Ruthardt et al, 1997). Notably, the biological e ects of the mutants are in agreement with their RAdependent transcription factor action, since biologically active mutants have a transactivating activity similar to that of PML/RARa and increased with respect of that of RAR.…”
Section: Discussionsupporting
confidence: 92%
“…Expression of PML/RARa into di erent haematopoietic cell lines revealed that the fusion protein is capable of mediating the di erentiative response to RA (Grignani et al, 1993;Ruthardt et al, 1997). Here, we investigated the molecular mechanisms underlying the biological activity of the fusion protein on RAsignalling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridization was performed in 50% formamide at 428C for 24 h with 32 P-labelled DNA probes followed by washes in 0.26SSC/0.1%SDS at 658C. Western blottings were performed on 100 mg of cellular lysates with a ± btubulin (Amersham), CP74 a-p21 (Dynlacht, 1997) and G3-245 a-RB (Pharmingen) monoclonal antibodies, and with the M2 a-CDK2, C-19 a-p27, H-432 a-cyclin A (Santa Cruz Inc), a-RARaF1 (Ruthardt et al, 1997) polyclonal antibodies. 500 mg of cell lysate were immunoprecipitated with 5 ml of M2 a-CDK2 antibody and the recovered immunocomplexes used for kinase assay using histone H1, as described (Xiong et al, 1993).…”
Section: Northern and Western Blots Immunoprecipitations And Kinase mentioning
confidence: 99%
“…Several experimental ®ndings indicate that both the leukaemogenetic e ect of PML/RARa and its ability to mediate RA-sensitivity are due to interference of the fusion protein with the program of terminal di erentiation: (i) before the onset of leukemias, the PML/RARa transgenic mice show a pre-leukemic condition characterized by increased and poorly di erentiated hematopoietic precursors in the bonemarrow (Brown et al, 1997a); (ii) expression of PML/ RARa in hematopoietic precursor cell lines blocks di erentiation induced by physiological stimuli (Grignani et al, 1993); (iii) RA induces differentiation of PML/RARa-expressing cells, both in the patients (Grignani et al, 1994) and in transgenic mice (Brown et al, 1997a;Grisolano et al, 1997;LiZhen et al, 1997); (iv) expression of PML/RARa in resistant or poorly RA-sensitive cell lines restores a di erentiative response to RA (Grignani et al, 1993;Ruthardt et al, 1997). It appears, therefore, that PML/RARa blocks di erentiation at physiological concentrations of RA, while it favours it at pharmacological doses.…”
Section: Introductionmentioning
confidence: 99%